Development and Evaluation of a Framework for Authentic Online Co‐Design: Partnership‐Focussed Principles‐Driven Online Co‐Design - Free Coulston; Alicia Spittle; Cassie McDonald; Rachel Toovey; Kate L. Cameron; Kimberley Attard; Loni Binstock; Isaac Fletcher; Adie Delaney; Tayla Murphy; Caroline Keating; Kath Sellick (Wiley, 2024)
ABSTRACT Introduction Co‐design in health research involves patient and public involvement and engagement (PPIE) in intervention or service design. Traditionally, co‐design is undertaken in‐person; however, exploring online delivery is warranted. PPIE in co‐design must be considered carefully, and assumptions that in‐person approaches will transition automatically to an online environment should be avoided. Currently, there are a lack of evidence‐informed approaches to facilitating co‐design online. This study aimed to develop and evaluate a framework for authentically adapting health research co‐design into an online environment. Materials and Methods The initial framework was developed through a literature review, synthesis of in‐person co‐design principles, and alignment of online strategies. The framework was then applied to a co‐design project with 10 participants across relevant PPIE groups (end‐users [n = 4], clinicians [n = 2], coaches [n = 2] and clinician−researchers [n = 2]). Participants' experiences of the online co‐design process were evaluated via a mixed‐methods design using surveys and semi‐structured interviews. Evaluation data were analysed using descriptive statistics and reflexive thematic analysis to inform a revised framework. Results The developed framework, Partnership‐focussed Principles‐driven Online co‐Design (P‐POD) was used to design eight 90 min online co‐design workshops. Evaluation data involved 46 survey responses, and eight participants were interviewed on project completion. Survey data indicated that the process was satisfying, engaging and adhered to the P‐POD framework. Themes derived from interview data describe a respectful and collaborative online culture, valuing of diverse perspectives and space for healthy debate, how power was perceived as being shared but not equal and multiple definitions of success within and beyond the process. A final, refined P‐POD framework is presented. Conclusion With evaluation of the initial P‐POD framework showing evidence of adherence to co‐design principles, positive participant experiences and goal achievement for both the project and the participants, the refined P‐POD framework may be used and evaluated within future intervention or service design. Patient or Public Contribution This study involved the participants (end‐users, clinicians and service providers) in the co‐design process described, interpretation of the results through member‐checking interview responses, assisting in development of the final framework and as co‐authors for this manuscript.